Self-medication with Antibiotics in Health Science and non-Health Science University Students - Gloria Fuentes Carrillo (Colegio de Enfermería de Caceres, 2017)
Self-medication is a very common practice in the Spanish university cohort due to the easy accessto medicine both with and without a medical prescription, which can cause numerous health problems dueto irresponsible use of pharmaceutical drugs and the masking of symptoms that could be indicative ofmajor diseases. The therapeutic breach or the abuse of antibiotics in this group can produce bacterialresistance and generate a great cost to health services. This descriptive study utilizes 135 students fromthe University of Extremadura (Spain) divided by Health Science and non-Health Science programs forwhich a survey was provided online to gather information on the population and the most common habitsof self-medication in order to determine the need for programs on health education and to determine theinformation that students possess on the rational use of these medicines. The results showed highpercentages of self-medication with antibiotics in students who lived in their family's home and tookcourses in non-Health Science studies due to disinformation concerning basic pharmacology. In addition,antibiotic treatment was abandoned in 89% of cases when symptoms disappeared. In conclusion,non-health sciences students demonstrate misperceptions and limited knowledge about the correct use ofmedicines. Students who self-medicate with antibiotics are more likely to live in their family home andhave non-health sciences areas of study. They are also more likely to stop antibiotic treatment early oncethe symptoms for which they took the medication resolve. This could be related to the lack of informationabout the correct use of medicines. Programs in health education in schools and a greater presence ofnursing in the education of children could cause a shift in behavior in future generations.